Physiological Factors Associated with Weak Neonatal Poults (Meleagris gallopavo) - Christensen, Vern L.; Ort, Debbie T.; Grimes, Jesse L. (International Journal of Poultry Science, 2002)
Management related deaths in turkey hatchlings remain a problem for turkey growers. The etiologies of such deaths also remain obscure. The hypothesis proposed by the current study was that weak poults identified by their characteristic flip-over behavior would differ physiologically from normal poults in a way that interferes with development of critical systems such as the cardiovascular and nervous system. Eight groups of 500 poults (from a 20-wk laying cycle) of the same breeder flock were examined. Each placement was in the same brooder house operated at identical conditions. Observations of `flip-over` poults were made at 6-h intervals for the initial wk of age. Identified poults (n = 12) were sacrificed and sampled immediately. Flip-over poults differed from controls only in depressed heart weight and plasma thyroid hormone concentrations. The identified poults did not differ from controls in body weight, liver weight, yolk weight, blood glucose or organ glycogen concentrations. In a second trial, reduced heart weights were noted along with reduced capability to maintain cardiac glycogen concentrations. The reduced heart weight or function may result in failure to provide nutrients for proper brain function. The data suggest that management to aid weak neonatal turkey poult deaths may need to focus on conditions fostering heart growth and function.